(untitled) (El Taco en la Brea, 2021)
propose a genealogical itinerary through central texts for literary studies in order to focus on the problem of critical distance as a paradoxical and constitutive ideologeme. For this I propose three scansions; first, a review of the founding texts of Russian formalism together with Benjaminian interventions in the first decades of the 20th century; then an approach to the renewals of critical language around the space of the magazine Tel Quel and the beginning of the Agambenian proposal; finally, a review of the topicality of the critical essay and negativity in Damián Tabarovksy y Alberto Giordano, contemporary Argentine writers. The tour focuses on various cultural scenes and moments in order to corroborate the persistence of the problem of distance and negativity, notions that offered an epistemological framework for experimentalism and the modulations of critical writing. When observing these interventions it is possible to notice a zone of indistinctions between thought and literary practices, in which criticism develops an immanent politics.